Joannsin, a novel Kunitz-type FXa inhibitor from the venom of Prospirobolus joannsi - Luan, Ning; Zhou, Chunling; Li, Pengpeng; Ombati, Rose; Yan, Xiuwen; Mo, Guoxiang; Rong, Mingqiang; Lai, Ren; Duan, Zilei; Zheng, Ruiqiang (Thrombosis and Haemostasis, 2017)
The repugnatorial glands of millipedes release various defensive chemical secretions. Although varieties of such defensive secretions have been studied, none of them is protein or peptide. Herein, a novel factor Xa (FXa) inhibitor named joannsin was identified and characterised from repugnatorial glands of Prospirobolus joannsi. Joannsin is composed of 72 amino acid residues including six cysteines, which form three intra-molecular disulfide bridges. It is a member of Kunitz-type protease inhibitor family, members of which are also found in the secretory glands of other arthropods. Recombinant joannsin exhibited remarkable inhibitory activity against trypsin and FXa with a Ki of 182.7 ± 14.6 and 29.5 ± 4.7 nM, respectively. Joannsin showed strong anti-thrombosis functions in vitro and in vivo. Joannsin is the first peptide component in millipede repugnatorial glands to be identified and is a potential candidate and/or template for the development of anti-thrombotic agents. These results also indicated that there is Kunitz-type protease inhibitor toxin in millipede repugnatorial glands as in other arthropods secretory glands.
Keywords: Millipede; repugnatorial gland; Kunitz-type inhibitor; factor Xa; thrombosis